1996
DOI: 10.1006/dbio.1996.0022
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Maturation of the Calcium Release Apparatus in Developing and Adult Avian Myocardium

Abstract: Muscle fibers release large amounts of calcium from an internal compartment, the sarcoplasmic reticulum (SR), during activation. Two proteins are involved in this process and its control: plasma membrane calcium channels, or dihydropyridine receptors (DHPRs), and SR calcium release channels, or ryanodine receptors (RyRs). The two proteins form part of a structural complex, perhaps unique to muscle cells, which allows an interaction between plasma membrane and SR, resulting in calcium release from the latter. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 0 publications
10
86
1
1
Order By: Relevance
“…Efficient calcium handling is essential in myocyte organization as the correct t-tubular system orientation is dependent on calcium signaling during development for example [39][40][41]. Therefore, disrupted calcium signaling may predispose to myocyte disarray.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient calcium handling is essential in myocyte organization as the correct t-tubular system orientation is dependent on calcium signaling during development for example [39][40][41]. Therefore, disrupted calcium signaling may predispose to myocyte disarray.…”
Section: Discussionmentioning
confidence: 99%
“…embryonic myocardium [43], possibly compromised by increased calcium sensitivity [40] and/or slower calcium re-uptake owing to immature excitation-contraction coupling [44,45]. As the sarcomere realignment occurs largely during the relaxation phase, this might lead to an increased instability of both sarcomere lengths along the fiber as well as the central position of A-bands.…”
Section: Correlation Of Myomesin and Titin Isoformsmentioning
confidence: 99%
“…Characterisation of Ca 2+ signalling in ventricular myocytes from animals such as fish (Shiels and White, 2005) has demonstrated that their responses resemble those of mammalian atrial cells. Non-mammalian ventricular cells largely display junctional couplings of VOCCs and RyRs around the cellular periphery (Protasi et al, 1996;Sommer and Jennings, 1992). Peripheral initiation and centripetal propagation is therefore the most commonly observed cardiac Ca 2+ signalling paradigm within biology.…”
Section: The Relevance Of Atrial Myocyte Camentioning
confidence: 99%